Wokół warszawskiego okresu życia i twórczości Władysława Żeleńskiego. Dokumenty epistolarne z lat 1873–1880 - Grzegorz Zieziula (Muzyka)
This study encompasses an edition of nine letters documenting the Warsaw period in the life and artistic career of Władysław Żeleński. There are letters from Żeleński’s outgoing and incoming correspondence (to Bohumil Pazdírek, Julian łukaszewski and Władysław Górski), evidence of the epistolary polemic that he carried on with Józef Brzowski on the pages of Warsaw’s daily press, and letters sent by the composer’s first wife, the writer, columnist and educationist Wanda Żeleńska (née Grabowska; 1841–1904), to Władysław Górski and his wife Helena (née Rosen), and to Izabela Zbiegniewska.